Identification and characterization of Colletotrichum spp. causing anthracnose in avocado Nayarit, Mexico - Trinidad-Ángel, Eddy; Ascencio-Valle, Felipe de Jesús; Ulloa, osé Armando; Ramírez-Ramírez, osé Carmen; Ragazzo-Sánchez, Juan Arturo; Calderón-Santoyo, Montserrat; Bautista Rosales, Pedro Ulises (Revista Mexicana de Ciencias Agrícolas, 2017)
Anthracnose caused by Colletotrichum spp. is one of the major diseases of avocado that affects the quality of its fruit and reducing production. Difficulties in controlling and eradicating the disease have been reported in previous years. Therefore, the objective was to identify and characterize Colletotrichum spp. strains as causal agent of anthracnose in the ‘Hass’ avocado through morphological, pathogenic and molecular studies, which were isolates from the principal production zones of avocado in the state of Nayarit, Mexico. Fruits with typical disease symptoms were collected from four communal lands belonging to Xalisco and Tepic, in Nayarit, Mexico. A collection of 20 isolates was obtained, which 13 were identified as C. gloeosporioides , one of C. hymenocallidis , five of C. siamense and one of C. tropicale , where the most pathogenic was a strain of Colletotrichum siamense and a strain of Colletotrichum gloeosporioides. It is important to note that it is the first report of C. hymenocallidis and C. siamense in avocado.
Keywords: avocado fruit, diversity, pathogenicity, variability